Quantitative Volumetric Imaging and Clinical Outcome Characterization of Symptomatic Concussion in 10- to 14-Year-Old Adolescent Athletes. Issue 6 (November 2018) - Mac Donald, Christine L.; Barber, Jason; Wright, Jason; Coppel, David; De Lacy, Nina; Ottinger, Steve; Peck, Suzanne; Panks, Chris; Zalewski, Kody; Sun, Samantha; Temkin, Nancy
Abstract : Objective: Prior work suggests that younger athletes may be more vulnerable to postconcussive syndrome. We investigated measures of clinical outcome and quantitative volumetric imaging in 10- to 14-year-old adolescent athletes to better understand the impact of concussion on this younger population. Setting: Outpatient clinics. Participants: Ten- to 14-year-old symptomatic pediatric sports concussion patients and typically developing active controls. Design: Prospective, observational multiclinic study. Main Measures: Demographics, magnetic resonance imaging, clinical assessments (neurocognitive function, postconcussive symptoms, mental health symptoms, quality of life). Results: Neuropsychological performance was comparable between groups while symptoms of mental health were discriminating and comprised the top regression model describing factors related to overall health behavior impairment. Concussion patients had smaller total brain volume as well as total intracranial volume in comparison with controls even though there was no difference on measures of natural development (age, height, weight, education, gender, and handedness). Conclusions: Findings indicate that 10- to 14-year-old concussion patients symptomatic at 1 month more likely exhibit mental health symptoms impairing health behavior than cognitive dysfunction. There may be a vulnerability for those with smaller brain volumes at the time of the exposure. The study provides new data to support further investigation into risk factors for prolonged symptoms in this younger athlete population.